Surface exchange and bulk diffusion properties of Ba0.5Sr 0.5Co0.8Fe0.2O3-d mixed conductor - Chen, D.; Shao, Zongping (2011)
Ba0.5Sr0.5Co0.8Fe0.2O 3-d (BSCF) is a mixed conducting oxide that shows high oxygen permeability to perform as a ceramic membrane and high electrochemical activity for oxygen reduction to perform as a cathode of solid oxide fuel cells. Both performances are closely related to the bulk and surface properties of the BSCF oxide. In this study, the chemical bulk diffusion coefficient (Dchem) and chemical surface exchange coefficient (kchem) of BSCF at various temperatures and oxygen partial pressures are determined by an electrical conductivity relaxation (ECR) method. Both Dchem and kchem are found to be dependent on pO12 with positive effect. Ea of D chem and kchem are respectively 111 ± 5 and 110 ± 6 kJ mol-1 between 600 and 800 °C. Oxygen-ion diffusion and tracer diffusion coefficients are estimated from Dchem and compared with the literature results. Ionic conductivities are further derived according to the Nernst-Einstein relation. The poisoning effect of CO 2 on the performances of BSCF is further investigated by the ECR method in combination with oxygen temperature-programmed desorption technique. The presence of CO2 causes a substantial decrease in k chem, however, the surface kinetics can be recovered by performing re-calcination in an oxidative atmosphere at 900 °C, agreeing well with literature reports.